Satellite Imageries for Supporting Tourism Development in Indonesia - Wati, Sri Eka; Narieswari, Lalitya (Badan Informasi Geospasial in Partnership with MAPIN, 2011)
Tourism is one of important sectors which support human life. It is basically defined as peopleâs activities to go to a certain interesting place during leisure time or holiday season. The attractive place offers some benefits to visitors, especially in relation with relaxation purpose. Tourism activities also play a role as one of the potential sectors influencing the development of a certain area and total of local income. In this case, tourism activities significantly affect the increasing of supporting facilities, for instance food stall, cottage, transportation line, etc. Furthermore, the number of visitors directly affects the total of regional income obtained from retribution fee and tax of each tourism object. Based on these reasons, local government tries to promote the existing tourism objects in order to increase both local and national income.Bangka Belitung Islands, one of the provinces in Indonesia, has beautiful scenery which attracts a lot of foreign and domestic tourists. More than 40 interesting places located at six regencies and a city under administrative authority of Bangka Belitung Islands Province offer unforgettable moment. Most of them are natural objects, for instance beach, hot spring water, and lake. Unfortunately, the number of visitors in this area is quite low comparing with other provinces in Indonesia. Thus, this condition requires the improvement of promotion action to attract the national and international visitors.Tourism promotion activities were generally done by developing tourism book, booklet, leaflet, and tourismâs website. The contents were map, photo, and description of tourism object related to location, history, and supporting facilities. In line with the development of Remote Sensing (RS) application, tourism object can be also exposed through satellite imageries. Some satellite imageries covering the area of Bangka Belitung Islands were processed to obtain several enhanced images. Landsat images were processed into composite band of 452, 321, 432, and 542 whereas Quickbird images were presented in natural color. Those processed images were utilized to visualize the present tourism objects in this province whether in terms of location and distribution as well. All information was subsequently presented through a book called Tourism Atlas from Space of Bangka Belitung Islands Province. The book becomes one of the supporting tools to promote tourism objects in this province.Key words: Satellite Imageries, Tourism,Â Bangka Belitung Islands- IndonesiaABSTRAKPariwisata merupakan salah satu sektorÂ penting yang mendukung kehidupan manusia. Selain menawarkan relaksasi bagi pengunjung,Â kegiatan pariwisatajuga berperansebagaisalah satu sektorpotensialyang mempengaruhi perkembangandaerah tertentu dantotalpendapatan daerah. Jumlah pengunjungsecara langsung mempengaruhitotalpendapatan daerahyang diperoleh dariretribusidan pajakdari setiapobjek wisata. Kepulauan Bangka Belitungmemiliki pemandangan indahyang menarikbanyakwisatawan asingdan domestik. Lebih dari40tempat-tempat menarikyang terletak dienamkabupatendan kotadi bawahadministrasiProvinsi KepulauanBangka. Sayangnya, jumlahpengunjung di daerahini cukup rendahdibandingkandengan provinsi lainnyadi Indonesia. Kondisi initentunya membutuhkanpeningkatanaksipromosiuntuk menarikpengunjungnasional daninternasional.Kegiatanpromosi pariwisataumumnyadilakukan dengan mengembangkanbukupariwisata,buku, leaflet, dansituspariwisata. Isinyapeta,foto,dan deskripsiobyek wisatayang berhubungan dengan lokasi, sejarah, danfasilitas pendukung. Sejalandengan perkembanganaplikasi Penginderaan Jauh, objekwisata juga bisa diekspose menggunakan citra satelit.Beberapacitra satelit(Landsat, Quickbird) meliputi wilayahBangkaBelitungKepulauandiprosesuntuk mendapatkan visualisasi yang lebih baik. Gambar tersebutdiprosesdipergunakan untukmemvisualisasikanobjek-objek wisatayang ada di provinsi inibaik dalamhal lokasidan distribusi.Semua informasikemudiandisajikan melaluibuku berjudulAtlasPariwisatadariRuangProvinsiKepulauan Bangka Belitung. Buku inimenjadisalah satu alatpendukung untukmempromosikanobyek wisatadi provinsi ini.Kata Kunci: Citra Satelit, Pariwisata, Pulau Bangka Belitung -Indonesia